(untitled) (Research, Society and Development, 2022)
Species of the genus Staphylococcus are among the main causative agents of nosocomial infections, and is particularly worrisome the increasing multidrug-resistant strains circulating in hospital settings, colonizing and infecting patients and healthcare staff. Secondary infections are an important aggravating factor in COVID-19. The aim of this review manuscript is to analyze through current scientific literature the impact of concomitant infection by species of the genus Staphylococcus among patients with COVID-19. The analysis of the current scientific literature allows us to infer that there is a large heterogeneity regarding the incidence of this co-infection/superinfection/colonization. Heterogeneity was also found regarding antibiotic resistance levels of the isolated Staphylococcus strains and divergent trends regarding the temporal incidence of this bacterial pathogen in infections secondary to COVID-19. These differences probably reflect local patterns, such as resistance profiles and secondary infections prior to the pandemic, as well as the levels of hospital infection control at each healthcare facility. Factors such as length of stay, use of mechanical ventilation, superinfection with hospital-circulating strains of Staphylococcus spp. directly impact secondary infection rates and prognosis in patients with COVID-19. Even considering the heterogeneity of the results, death rates can be considered high in patients presenting concurrent Staphylococcus spp. infection in the severe form of the SARS-CoV-2 disease, with rates that can surpass 90%.